Quantitative comparison of chiral catalysts selectivity and performance: A generic concept illustrated with cyclododecanone monooxygenase as baeyer-villiger biocatalyst - Fink, Michael J. (2012)
Contribución equivalente como primer autor: Fink, Michael J. y Rial, Daniela V. Within this work a generic tool for chiral catalyst evaluation is established based on the application-oriented properties activity and selectivity; the concept aims at quantitatively comparing catalyst performance in general on a multitude of substrates. It is designed and intended to serve as decision guidance for challenges in catalysis and comprehensible information extraction from already recorded but unrefined data sets. The underlying algorithm assigns function points to catalytic entities via a statistically solid model possessing high flexibility and generates a relative ranking. This is coupled to an automated iterative refinement process towards maximum information content of results employing Shannon entropy optimization. Consequently, the developed workflow facilitates high distinguishability between catalysts even in low-scattering data sets. The numerical ranking is complemented by a clearly arranged graphic representation permitting facile and reliable visual interpretation of generality or niche capabilities of catalysts. Usefulness of the title concept is demonstrated by the performance evaluation of cyclododecanone monooxygenase, a highly versatile Baeyer-Villiger enzyme. To retain broad applicability, an open-source MATLAB® script is provided in electronic form.